Non-Pharmacological Strategies Pain Management in Patients on Dialysis Therapy - Abdul Adheem, Dr. Fadhil Muslim; Al Bermani, Dr. Khaled Abdulsatar Mahdi Al Bermani; Al Janabi, Dr. Mohammed Sami Noori Al Janabi (Academic Journal of Clinicians, 2023)
Background: Pain is considered a public health problem due to its high prevalence in the world and its economic and personal costs, not only for those who suffer from it, but also the society. Objective: to identify the impact of non-pharmacological strategies on pain management in patients in hemodialysis therapy. Patients and method: Quasi-experimental pilot research where pre- and post-measurements of the brief inventory of pain in patients on renal replacement therapy, who received education in non-pharmacological strategies for pain management. Results: significant changes in the item of the perception of pain in the last 24 hours, since at the first measurement the average is 6.27 and in the second of 4.45, according to the pain inventory this means that there was a perception of lower pain in the last 24 hours in the measurement after the management sessions of the pain with non-pharmacological strategies. significant changes in the item of "enjoy life”, since in the first measurement the average is 4.82 and in the second 3.73 according to the pain inventory this means that patients perceived a lower inference from pain to enjoy life. Conclusion: Non-pharmacological pain management strategies are low-cost, safe and non- invasive, which decreases the side effects and increases the autonomous role of the patient in therapy. In cases of mild pain it can be a tool to manage pain in its entirety and in other cases of severe pains it can be used together with the conventional pharmacological treatment.